HUBUNGAN KADAR TRANSFORMING GROWTH FACTOR BETA DENGAN DERAJAT NYERI PADA MIGRAIN DAN TENSION-TYPE HEADACHE - Ningsih, Nadya Ayu; Surbakti, Khairul Putra; Pujiastuti, R. A. Dwi (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
ABSTRACT Introduction: Primary headaches, which mainly include Tension-type Headache (TTH) and migraine, account for 90% of all headaches and are the leading cause of disability worldwide. Migraine and TTH have pathogenesis that is not fully known, with one theory proposing neurogenic inflammation. Human Transforming Growth Factor Î² (TGF-Î²) is a pro-inflammatory cytokine that is thought to be involved in the occurrence of migraine and TTH. Objective: To determine the correlation between human TGF-Î² levels and the pain severity in migraine and TTH. Methods: This study used a cross-sectional design in patients with a diagnosis of migraine and TTH who sought treatment at the Ambulatory Clinic of Adam Malik Hospital and Prof. Dr. Chairuddin P. Lubis Hospital. We use Numeric Rating Scale score to determine the pain severity and ELISA kit to measure the TGF-Î² levels. This study involved 30 patients who met the inclusion and exclusion criteria. Results: The study subjects were found to be mostly female, 22 people (73.3%), with the age range of 18 to less than 26 years which was 20 people (66.7%). The mean TGF-Î² level of patients was 0.400Â±0.531 ng/mL. The mean pain severity of patients was 2.60Â±2.415. The results of the Spearman correlation test showed a moderate positive correlation (r: 0.523) which was found significant with a p value of 0.003 between TGF-Î² and the pain severity in migraine and TTH. Conclusion: There was significant correlation between human TGF-Î² levels and pain severity in migraine and TTH. Keywords: migraine, pain severity, TGF-Î², TTH